Analyzing Socioeconomic Impacts of Strategic Planning for Social Entrepreneurs - Raj, Shekhar (Digital Repository of Theses - SSBM Geneva, 2025)
Through this thesis, the socio economic implications of strategic planning of social entrepreneurs is examined, in terms of how a planned process affects long term sustainability, expansion, and creation of social value (in the form of employment generation particularly). Social entrepreneurship (SE) has become an important way to respond to many socioeconomic problems by using business resources and it has a social purpose. However, the role that the formal strategic planning plays an influencing role in the socio economic outcomes of social enterprises which still has a knowledgegap even though its contribution has been increasing. Our thesis is based on theoretical perspective from the Resource Based View (RBV) and Social Resource Based View (SRBV) to formulate and empirically justify a conceptual framework linking innovation, strategic planning and employment generation. The study focus on (1) the identification of issues of major things practiced by social entrepreneurs in strategic planning process, (2) evaluation of the socio economic effects of such practices, (3) comprehension of the problems that are experienced by the social entrepreneurs in their pursuit of the socio economic impacts and (4) the description and testing of a model which facilitate the analysis of the relationship between the planning and outcomes. A mixed method approach have been used in this study. The qualitative insightswere gathered using 32 semi structured interviews with social entrepreneurs in the healthcare, financial and real estatesector. In the quantitative part of the research, 101 social enterprise managers and employees were surveyed to measure constructs such as innovation, strategic planning, and employment generation. The analysis was done using PLS SEM (Partial Least Squares Structural Equation Modeling) and thus, highly complex relationships and predictive dynamics have been evaluated.The results put much emphasis on the fact that innovative planning practices have a positive influence on long term strategic thinking and complete planning has been observed to greatly enhance the socio economic effects of social enterprises particularly when it comes to creation of jobs. The findings also demonstrate the importance that context, institutional resources, and resource availability also plays an important role.The study contributes to both theory and practice because the research demonstrates that structured and innovative planning can help social entrepreneurs to develop robust enterprises that offer long-term positive impacts on their society. It establishes practical solutions to social enterprises, funders, and policy formulators, establishing a tighter link between social enterprise strategies and socio economic outcomes.